2017
DOI: 10.1038/s41598-017-10521-9
|View full text |Cite
|
Sign up to set email alerts
|

In search of a small molecule agonist of the relaxin receptor RXFP1 for the treatment of liver fibrosis

Abstract: The peptide hormone human relaxin-2 (H2-RLX) has emerged as a potential therapy for cardiovascular and fibrotic diseases, but its short in vivo half-life is an obstacle to long-term administration. The discovery of ML290 demonstrated that it is possible to identify small molecule agonists of the cognate G-protein coupled receptor for H2-RLX (relaxin family peptide receptor-1 (RXFP1)). In our efforts to generate a new medicine for liver fibrosis, we sought to identify improved small molecule functional mimetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
(60 reference statements)
0
18
0
Order By: Relevance
“…[117] The small molecule, ML290, has been described as an RXFP1 agonist, resulting in increased cAMP levels and reduced collagen I gene expression in chronic liver disease. [118] In addition, ML290 has been shown to have similar signaling responses as RLX (e.g. increased cAMP through certain G-coupled proteins, p38MAPK, MMP-2, pSMAD2 and cGMP), while they differed in active p-ERK1/2 levels, though, interestingly, priming with ML290 enhanced…”
Section: Relaxin Mimeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…[117] The small molecule, ML290, has been described as an RXFP1 agonist, resulting in increased cAMP levels and reduced collagen I gene expression in chronic liver disease. [118] In addition, ML290 has been shown to have similar signaling responses as RLX (e.g. increased cAMP through certain G-coupled proteins, p38MAPK, MMP-2, pSMAD2 and cGMP), while they differed in active p-ERK1/2 levels, though, interestingly, priming with ML290 enhanced…”
Section: Relaxin Mimeticsmentioning
confidence: 99%
“…ML290 appears to be an RXPF1 agonist in humans, monkey's and pigs, and an antagonist in mice, suggesting species bias in ML290 signaling. [118,119,120] However, studies with mouse RXFP1 replaced with humanized RXFP1 have shown that animal models can be developed to study the effects of ML290 in smaller rodents. [121] In contrast to RLX, ML290 has been shown to have a half-life in the heart and plasma of ~8 hours, opening the possibility of longer lasting effects with less treatment time.…”
Section: Relaxin Mimeticsmentioning
confidence: 99%
“…Similar results have been recently reported by another group in the HSC LX-2 cell line using ML-290. 29…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we demonstrated that despite lower activity in the cAMP assay, ML290 showed higher efficacy in other relaxin‐dependent cellular and gene activation tests than several other compounds in this series (20). Here, we tested 5 different compounds to select the agonist most effective at targeting expression of several genes involved in remodeling of ECM in primary HSCs (22, 30). ML290 consistently suppressed COL1A1 and TGFB1 expression and up‐regulated the previously established relaxin target PPARGC1A (38).…”
Section: Discussionmentioning
confidence: 99%